2013
DOI: 10.1093/hmg/ddt496
|View full text |Cite
|
Sign up to set email alerts
|

AIPL1, A protein linked to blindness, is essential for the stability of enzymes mediating cGMP metabolism in cone photoreceptor cells

Abstract: Defects in the photoreceptor-specific gene encoding aryl hydrocarbon receptor interacting protein like-1 (AIPL1) are linked to blinding diseases, including Leber congenital amaurosis (LCA) and cone dystrophy. While it is apparent that AIPL1 is needed for rod and cone function, the role of AIPL1 in cones is not clear. In this study, using an all-cone animal model lacking Aipl1, we show a light-independent degeneration of M- and S-opsin containing cones that proceeds in a ventral-to-dorsal gradient. Aipl1 is nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…AIPL1 is essential to maintain the stability of PDE6a and PDE6b (Ramamurthy et al 2004; Kolandaivelu et al 2009; Kolandaivelu et al 2014). As predicted, our proteomics analysis detected no PDE6b.…”
Section: 4 Discussionmentioning
confidence: 99%
“…AIPL1 is essential to maintain the stability of PDE6a and PDE6b (Ramamurthy et al 2004; Kolandaivelu et al 2009; Kolandaivelu et al 2014). As predicted, our proteomics analysis detected no PDE6b.…”
Section: 4 Discussionmentioning
confidence: 99%
“…The Nrl -/ -Aipl1 -/ -mouse was used to investigate the mechanism of cone cell death in AIPL1 LCA. 46 Investigators found that the Aipl protein was essential for the stability of retGC1 in cones and that, in its absence, retGC1 trafficking was defective, cGMP was decreased, and cones were lost much more rapidly than in Nrl -/ -controls. 46 Authors speculated that cone death in the Nrl…”
Section: Gucy2ementioning
confidence: 99%
“…[42][43][44] Utilizing the Nrl -/ -mouse as a genetic background on which to examine other mutations/alleles associated with cone dysfunction has been useful for understanding the mechanisms of cone degeneration in various forms of achromatopsia and LCA, as well as modeling retinal dystrophies with unique foveal presentation, for example, CEP290-LCA. [45][46][47] We recently crossed the GC1KO mouse onto an Nrl -/ -background, thereby creating an all-cone model of retGC1 deficiency. The purpose of our study was to determine the impact of AAV-mediated retGC1 expression on cone structure and function and cone-mediated visual behavior in the Nrl -/ -Gucy2e -/ -mouse, a model with a retina containing a high density of exclusively cone photoreceptors.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse models with selective ablation of AIPL1 in cones also show highly reduced levels of cone PDE6 and cone photoreceptor degeneration, albeit at a slower rate compared to rods lacking the chaperone [24, 25]. Interestingly, in an all-cone mouse model lacking AIPL1, retinal guanylate cyclase-1 (RetGC1), which mediates synthesis of cGMP, is also dramatically reduced [26]. As a result, the levels of cGMP in this model are reduced, possibly accounting for the slower pace of degeneration of cones [26].…”
Section: Aipl1 Is a Specialized Chaperone Of Pde6mentioning
confidence: 99%
“…Interestingly, in an all-cone mouse model lacking AIPL1, retinal guanylate cyclase-1 (RetGC1), which mediates synthesis of cGMP, is also dramatically reduced [26]. As a result, the levels of cGMP in this model are reduced, possibly accounting for the slower pace of degeneration of cones [26]. Evidence for the direct effect of AIPL1 on stability or trafficking of RetGC1 is lacking, and the downregulation of RetGC1 in cones lacking AIPL1 might be secondary to the deficiency of cone PDE6.…”
Section: Aipl1 Is a Specialized Chaperone Of Pde6mentioning
confidence: 99%